Identification and Prioritization of Effective Factors in the Model of Emerging Sports with a Perspective on the Development of Mass Sports - Ghomi, Omid; Safania, Ali Mohammad; Farahani, Abolfazl; Nikbakhsh, Reza; Baqerian Farahabadi, Mohsen (Health Nexus, 2023)
Emerging sports, due to their increasing attractiveness among various age groups in society, are considered a novel path for enhancing physical activities within communities. The aim of this research is to design a model for the development of emerging sports with a perspective on the development of mass sports. Given the dimensions and type of research, the methodology was conducted with a mixed approach (qualitative and quantitative). In the qualitative section, the research strategy was exploratory and carried out using grounded theory methodology. In the quantitative section, the ANP method was used to prioritize factors. To extract factors, interviews were conducted with 13 experts selected based on purposive sampling method and theoretical saturation. Accordingly, four categories were presented: design of processes and infrastructures, characteristics of emerging sports, facilitators, and barriers to the development of emerging sports. Based on prioritization, operational infrastructures with a weight of 0.247 ranked first, management infrastructures with a weight of 0.212 in second priority, sports organizations as facilitators in third priority with a weight of 0.169, structural characteristics with a weight of 0.094 in fourth priority, performance characteristics with a weight of 0.080 in fifth priority, community as a facilitator with a weight of 0.074 in sixth priority, barriers in organizations with a weight of 0.063 in seventh priority, and barriers at the community level with a weight of 0.057 in eighth priority. Considering the findings of the research, it is suggested that the presented factors be utilized in the General Sports Federation for the development of emerging sports.